CALL FOR PAPER: "Linguistic, Metrical and Cognitive Implications in Sung Verse" (Rome, 23-25 February 2012) - Canettieri, Paolo; Proto, Teresa; Valenti, Gianluca (Cognitive philology, 2011)
The expression “sung verse” covers a wide variety of metrical-melodic forms which are found across time and space in all human cultures. They span from folk songs to Opera, from counting-out rhymes to epics, from courtly songs to rap. While in spoken verse the metrical pattern is grounded in the prosody of the language in which it is composed, in sung verse the overall metrical structure results from the matching of specific prosodic units of the text (moras, syllables, stress, etc.) to the rhythmic-melodic structure provided by the tune. This matching thus requires the coordination of two cognitive mechanisms, i.e. the musical and linguistic competence. The aim of the present conference is to bring together specialists from different research areas to discuss issues regarding the regulated, formal organization of sound and speech in sung verse.